Visible-light photo-Fenton oxidation of phenol with rGO-α-FeOOH supported on Al-doped mesoporous silica (MCM-41) at neutral pH: Performance and optimization of the catalyst. (September 2017) - Wang, Ying; Liang, Mingxing; Fang, Jiasheng; Fu, Jun; Chen, Xiaochun
Abstract: In this study, α-FeOOH on reduced graphene oxide (rGO-α-FeOOH) supported on an Al-doped MCM-41 catalyst (RFAM) was optimized for the visible-light photo-Fenton oxidation of phenol at neutral pH. The stability of the catalysts, effect of bubbling aeration, and degradation intermediates were investigated. Results indicated that RFAM with a large Brunauer-Emmett-Teller (BET) area and mesoporous structure displayed excellent catalytic activity for the visible-light-driven (VLD) photo-Fenton process. Phenol degradation was well described by a pseudo-first-order reaction kinetics model. Raman analysis demonstrated that an rGO-α-FeOOH (RF) composite is formed during the ferrous-ion-induced self-assembly process. Al-MCM-41 could uniformly disperse RF nanosheets and promote the mobility and diffusion of matter. The activity of the main catalyst α-FeOOH was enhanced after the incorporation of rGO nanosheets. The α-FeOOH crystal in RFAM showed catalytic activity superior to those of Fe3 O4 and Fe2 O3 . The RFAM catalyst, with an optimal GO-Fe 2+ mass ratio of 2.33, exhibited a larger BET area, pore size, and pore volume, and thus exhibited high performance and energy utilization efficiency in the VLD photo-Fenton reaction with remarkable stability. Bubbling N2 inhibited catalytic performance, while bubbling O2 or air only slightly accelerated the phenol degradation. Visible light played an important role in accelerating the formation of reactive oxygen species (·OH) for the highly efficient phenol degradation. Analysis of degradation intermediates indicated a high phenol mineralization level and the formation of low-molecular-weight organic acids. This work would be helpful in providing an insight into a new type of catalyst assembly and a possible route to a promising heterogeneous catalyst applicable in the visible light photo-Fenton process for effective wastewater remediation at neutral pH. Highlights: The catalyst RFAM displayed excellent catalytic activity for the VLD photo-Fenton process at neutral pH. Excellent capacity of RFAM ascribed to synergistic effects of α-FeOOH, rGO and the Al-MCM-41 support. The effects of the contents of loading and bubbling gas were studied. The energy utilization factor at different parameters and the degradation intermediates were studied.